Immunofluorescent localization of two different Na,K-ATPases in the rat retina and in identified dissociated retinal cells - McGrail, KM (J Neurosci, 1986)
Two isozymes of the Na,K-ATPase are made in the brain and retina. Antisera have been produced that contain antibodies specific for each of the catalytic subunits of the two isozymes, alpha and alpha(+) (Sweadner & Gilkeson, 1985a). To determine which classes of cells express which form of the Na,K-ATPase, and whether cells can express both forms, the antisera were used to stain sections of the rat retina and dissociated retinal cells by indirect immunofluorescence. In sections of the retina, bright stain specific for both isozymes was seen in the inner segments of the photoreceptor cells, the outer and inner plexiform layers, and in the ganglion cell axons. Cell bodies were outlined in the inner nuclear layer. Stain specific for the alpha isozyme was seen in adhering pigment epithelium and at the position of the apical processes of the Muller glial cells. In sections of the optic nerve, the nerve itself stained for both isozymes, although the stain for the alpha(+) isozyme was stronger. The sheath, in contrast, stained selectively for the alpha isozyme. Cells were dissociated from the retina, and they were identified by their morphology and by cell class-specific monoclonal antibodies. Muller glial cells were found to stain brightly for only the alpha isozyme, while horizontal and ganglion cells stained brightly for both isozymes. Bipolar cells stained faintly for only the alpha(+) isozyme, while amacrine cells stained faintly for both isozymes. The evidence indicates that different kinds of neurons can express one or both isozymes of the Na,K- ATPase, and at quantitatively different levels.